Development of a spaceborne pulse tube cooler operating at 170K. (July 2020) - Deng, Weifeng; Liu, Shaoshuai; Jiang, Zhenhua; Ding, Lei; Wu, Yinong
Highlights: A transient cosimulation of the pulse tube cooler was conducted based on the electric-mechanical-acoustic model. The effects of operating frequency and charging pressure on the cooling performance were investigated experimentally. A cooling power of 50 W at 170 K can be achieved with input power of 228 W and the measured specified Carnot efficiency is 15.8%. The performance of the PTC at 150K-200 K were shown and the measured acoustic power efficiency is above 76.8% at 170 K. Abstract: The Infrared Focal Plane Array (IRFPA) detector needs quite low dark noise for image detection. It can be cooled to demanding low temperature by pulse tube cooler (PTC) because of low vibration and low electromagnetic interference (EMI) at cold end. A high-capacity pulse tube cooler driven by a moving-magnet linear compressor is presented in this paper. The regenerator and pulse tube are arranged in coaxial. The inertance tube and reservoir are used as passive phase shifter of the PTC. A numerical thermodynamic model is established to design and optimize overall performance of the pulse tube cold finger aimed for the best efficiency. Based on the principle of electric-mechanical-acoustic coupling field, a transient co-simulation of the PTC is proposed. The mass of the PTC is less than 12 kg without electronic controller. The oscillating linear compressor has a pair of opposite pistons to eliminate vibration and the input electric input power is 400 W at maximum. A typical cooling performance of 50 W at 170 K has been achieved with 228 W input power at reject temperature of 293 K, provided by water cooling. The specified Carnot efficiency is 15.8%. Additionally, overall cooling performances of the PTC at 150K-200 K are investigated by experiment, Not only could this PTC be used for space mission but also a promising alternative to the domestic low temperature applications.